USTRUSHANA KITCHEN UTENSILS OF THE VII-VII CENTURIES - M. Pardaev; G. Muminova (Scholar Express Journals, 2022)
The basis of this article is information based on the history of the 7th-8th centuries in the Middle Sangzor irrigation oasis, the rural settlements of Kingirtepa, Almantepa II, the Lower Sangzor irrigation oasis, the rural settlements of Rasulboykultepa, Komilbobotep, Yakubbobotepa, Jumabobotepa and a description and analysis of pottery kilns taken from the layers of the city landmark Kalyatepa
Keywords: Rural areas of Kingirtepa; Almantepa II; Rasulboykultepa; Komilbobotep